Effects of Hydrophobicity on Antimicrobial Activity, Selectivity, and Functional Mechanism of Guanidinium‐Functionalized Polymers. Issue 7 (14th May 2021) - Tan, Jason; Zhao, Yanli; Hedrick, James L.; Yang, Yi Yan
Abstract: In this study, a series of guanidinium‐functionalized polycarbonate random co‐polymers is prepared from organocatalytic ring‐opening polymerization to investigate the effect of the hydrophobic side chain (ethyl, propyl, isopropyl, benzyl, and hexyl) on their antimicrobial activity and selectivity. Although the polymers exhibit similar minimum inhibitory concentrations, the more hydrophobic polymers exhibit a faster rate of bacteria elimination. At higher percentage content (20 mol%), polymers with more hydrophobic side chains suffer from poor selectivity due to their high hemolytic activity. The highly hydrophobic co‐polymer, containing the hydrophobic hexyl‐functionalized cyclic carbonate, kills bacteria via a membrane‐disruptive mechanism. Micelle formation leads to a lower extent of membrane disruption. This study unravels the effects of hydrophobic side chains on the activities of the polymers and their killing mechanism, providing insights into the design of new antimicrobial polymers. Abstract : A series of biodegradable guanidinium‐functionalized random polycarbonates, with varying hydrophobic side chains, is synthesized by organocatalytic ring‐opening polymerization. Despite being more efficient in eliminating bacteria, the more hydrophobic polymers suffer from poor selectivity due to high hemolytic activity. The increment in hydrophobicity has also changed the killing mechanism of the polymers to predominantly membrane disruption.